Halo mass estimates from the globular cluster populations of 175 low surface brightness galaxies in the Fornax cluster. Issue 4 (1st February 2019) - Prole, D J; Hilker, M; van der Burg, R F J; Cantiello, M; Venhola, A; Iodice, E; van de Ven, G; Wittmann, C; Peletier, R F; Mieske, S; Capaccioli, M; Napolitano, N R; et al.
Abstract: The halo masses M halo of low surface brightness (LSB) galaxies are critical measurements for understanding their formation processes. One promising method to estimate a galaxy's M halo is to exploit the empirical scaling relation between M halo and the number of associated globular clusters ( N GC ). We use a Bayesian mixture model approach to measure N GC for 175 LSB [23 ≤ 〈μ e, r 〉 (mag arcsec −2 ) ≤ 28] galaxies in the Fornax cluster using the Fornax Deep Survey data; this is the largest sample of low-mass galaxies so-far analysed for this kind of study. The proximity of the Fornax cluster means that we can measure galaxies with much smaller physical sizes [0.3 ≤ r e, r  (kpc) ≤ 9.5] compared to previous studies of the GC systems of LSB galaxies, probing stellar masses down to M * ∼ 10 5  M⊙ . The sample also includes 12 ultra-diffuse galaxies (UDGs), with projected r -band half-light radii greater than 1.5 kpc. Our results are consistent with an extrapolation of the M * − M halo relation predicted from abundance matching. In particular, our UDG measurements are consistent with dwarf-sized haloes, having typical masses between 10 10 and 10 11  M⊙ . Overall, our UDG sample is statistically indistinguishable from smaller LSB galaxies in the same magnitude range. We do not find any candidates likely to be as rich as some of those found in the Coma cluster. We suggest that environment might play a role in producing GC-rich LSB galaxies.